2005
DOI: 10.1103/physrevlett.95.035501
|View full text |Cite
|
Sign up to set email alerts
|

Single Impurity Effect on the Melting of Nanoclusters

Abstract: We show by molecular dynamics simulations that the melting temperature of clusters can be tuned by selective doping. In fact, a single Ni or Cu impurity in Ag icosahedral clusters considerably increases the melting temperature even for sizes of more than a hundred atoms. The upward shift is correlated to the strain relaxation induced by a small central impurity in icosahedral clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
170
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(183 citation statements)
references
References 31 publications
9
170
0
4
Order By: Relevance
“…For example, Mottet et al found that substituting a single nickel or copper impurity into icosahedral silver clusters causes a substantial increase in the melting temperature which can be attributed to the strain relaxation induced by sequestering the small impurity atom in the center of the icosahedron. 33 Cheng et al found a similar result for the substitution of a single copper atom in icosahedral Au 55 . 30 They also found that the copper segregates away from the surface in the liquidlike forms of Au 54 Cu and Au 43 Cu 12 .…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…For example, Mottet et al found that substituting a single nickel or copper impurity into icosahedral silver clusters causes a substantial increase in the melting temperature which can be attributed to the strain relaxation induced by sequestering the small impurity atom in the center of the icosahedron. 33 Cheng et al found a similar result for the substitution of a single copper atom in icosahedral Au 55 . 30 They also found that the copper segregates away from the surface in the liquidlike forms of Au 54 Cu and Au 43 Cu 12 .…”
Section: Introductionsupporting
confidence: 58%
“…A single atomic substitutional impurity may put the host lattice under additional stress, but it also may help to ameliorate the existing strain in the host metallic cluster. A specific example of this last situation, which tends to enhance the melting points of the doped clusters, has been shown by Mottet et al: 33 Introducing a copper impurity at the center position of an Ag 55 icosahedron significantly relaxes the strain of the host cluster because a copper atom is smaller than a silver atom. Note that in this special example the relaxation of the host lattice around the impurity is homogeneous, that is, involves the coherent contraction of the outer silver atomic shells without unevenly redistributing the remaining bond strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of catalytic performance have been shown on Pt-Ni nanoalloys, 1 where adding Ni atoms to the second atomic layer of a platinum surface dramatically increases the number of active sites for oxygen adsorption, and on tetrahexahedral Pt nanocrystals, 2 whose (730) high-index facet exhibits much enhanced catalytic activity. Thermal stability studies have shown that a single Ni or Cu atom doped into a Ag icosahedron 3 considerably increases the melting temperature for cluster size of 55, 147 and 527 atoms, and that the roughening of (110) facets 4 leads to the melting transition of the gold nanorod of 2624 atoms, showing that the stability of the nanorod is governed by the free energy of the surface facets. One previous study 5 of the structural characterization of size-selected gold clusters from scanning transmission electron microscopy (STEM) demonstrated that the real shapes of Au 309 clusters were defined by the surface facets, and the three-dimensional atomic-scale structures of Au 309 clusters can be identified with decahedral, cuboctahedral or icosahedral geometries.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the investigation by Jarrold et al revealed that the reactivity of Al clusters can be enhanced through cluster melting; 19 Mottet et al found the melting points of Ag clusters can be changed by doping; 20 The correlations with structural changes are often investigated to explore the melting behaviors of metal clusters in detail. For example, the distinct isomerization transitions occurred prior to its full melting for a 38-atom Co cluster; 21 Schebarchov et al found there is a structural change from the icosahedron to the decahedron in liquid-solid co-existing Ni cluster; 22 Wen et al specifically studied the shape transformation of a tetrahedral Pt cluster during its melting.…”
Section: Introductionmentioning
confidence: 99%